Analisis Semiotika Makna Motivasi dalam Lirik Lagu “1-800-273-8255” Karya Logic - Muhammad Irhamurrahman; Rina Juwita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
The phenomenon of mental health and suicide is still a sensitive issue that occurs throughout the world, therefore if no prevention is done, then sensitive cases like this will continue to take place. The rise of suicide cases that continue to increase every year makes this social phenomenon much raised in the world of art, such as songs. One of the songs that describes the phenomenon of mental health and suicide is the song with the title 1-800-273- 8255. This research aims to find out what motivational meaning is contained in the lyrics of the song 1-800-273-8255. This research uses interpretative qualitative research with Ferdinand de Saussure's semiotic method which divides the meaning of understanding into signifiers and signs through analysis in each stanza of the lyrics. The results of this study after dividing several stanzas in the song lyrics then divide the analysis into signifiers and signs to find the meaning of motivation contained in the song lyrics. The author found that the song